2006
DOI: 10.1103/physrevb.73.125428
|View full text |Cite
|
Sign up to set email alerts
|

Translational dynamics and friction in double-walled carbon nanotubes

Abstract: We report on a study of the translational sliding motion and dynamic friction in systems of double-walled carbon nanotubes using molecular dynamics simulations combined with theoretical analysis. The sliding motion is described by a one-dimensional analytical model which includes the van der Waals force between the nanotubes, a dynamic friction force, and a small Langevin-type fluctuating force. The dynamic friction force is shown to be linear in the velocity over a large domain of initial conditions in armcha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 26 publications
(38 reference statements)
3
66
0
Order By: Relevance
“…The ultralow friction observed by Cumings and Zettl 3 was further investigated by Guo et al, 4 Servantie and Gaspard, 5 and Rivera et al 6 The interlayer resistance force against sliding, although small when compared to the van der Waals force, can prevent sustained oscillation as a result of the friction induced energy dissipation. 4 Servantie and Gaspard 5 also concluded that friction is small relative to the van der Waals force, by two orders of magnitude.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The ultralow friction observed by Cumings and Zettl 3 was further investigated by Guo et al, 4 Servantie and Gaspard, 5 and Rivera et al 6 The interlayer resistance force against sliding, although small when compared to the van der Waals force, can prevent sustained oscillation as a result of the friction induced energy dissipation. 4 Servantie and Gaspard 5 also concluded that friction is small relative to the van der Waals force, by two orders of magnitude.…”
Section: Introductionmentioning
confidence: 91%
“…It has been shown by a number of researchers [3][4][5][6] that frictional forces are small in comparison to the van der Waals force, and in some cases by several orders of magnitude. 6 As a first approximation to this potential device we therefore ignore the effects of friction so that F r ͑Z͒ = 0.…”
Section: Oscillationmentioning
confidence: 99%
See 2 more Smart Citations
“…2a Before describing the theory leading to Fig. 2, it is also of interest to ask if F motor can overcome the dynamical friction between the two CNTs [15], [16], [17]. For a spinning CNT with carbon atoms of mass m c moving with a tangential velocity v c , the dynamical friction force per carbon atom is [17] ∞ (E) of equation (12), which is proportional to the total tangential velocity carried by all right-moving channels of energy E in an infinite (6,4) This demonstration that an "electron wind" can cause a chiral "CNT windmill" to rotate, could lead to range of applications [18].…”
mentioning
confidence: 99%